2012
DOI: 10.1186/1297-9716-43-29
|View full text |Cite
|
Sign up to set email alerts
|

What have we learned from brucellosis in the mouse model?

Abstract: Brucellosis is a zoonosis caused by Brucella species. Brucellosis research in natural hosts is often precluded by practical, economical and ethical reasons and mice are widely used. However, mice are not natural Brucella hosts and the course of murine brucellosis depends on bacterial strain virulence, dose and inoculation route as well as breed, genetic background, age, sex and physiological statu of mice. Therefore, meaningful experiments require a definition of these variables. Brucella spleen replication pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
219
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(234 citation statements)
references
References 167 publications
11
219
0
Order By: Relevance
“…The S19 also displayed early suppressive effects at 7 dpi before returning to concentrations consistent with naïve animals. The S19 IgG suppression is consistent with previous reports in this mouse strain (Grillo et al 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The S19 also displayed early suppressive effects at 7 dpi before returning to concentrations consistent with naïve animals. The S19 IgG suppression is consistent with previous reports in this mouse strain (Grillo et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…The murine model for B. abortus is well established and allows for efficient evaluation of the effect trypanosomes have on the host immune system (Montaraz and Winter 1986;Grillo et al 2012). Trypanosoma musculi was also evaluated in C57BL/6 mice and found to induce profound T-cell depression and anergy at 7 days postinfection (dpi) (Magluilo et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, based on a substantial data dedicated to standardize the mouse model for vaccine testing, a standardized protocol for controlling the quality of B. melitensis Rev.1 vaccines has been accepted by the World Organization for Animal Health [9]. The vaccine efficacy is generally analyzed 2 weeks after challenge, when the differences between the reference-vaccinated and unvaccinated controls have reached at maximum [7]. Considering these facts, goats were challenged 28 th day post vaccination and sacrificed 90 th day post challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The higher values of granulocyte in challenged animals indicated more virulence of organisms. The lymphocyte/granulocyte proportions in blood vary according to animal species and breed and may range in between 80/15 % to 90/9 % on Brucella infection [7]. It has been suggested that a phenotype may be related to Brucella clearance due to the regulatory action which neutrophils can display over macrophages [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation